PACK FEATURES AND AVAILABILITY OF ILLICIT TOBACCO PRODUCTS VIA THE INTERNET IN PAKISTAN - Mukhtar, Haseeba; Khan, Zohaib; Fayaz Ahmed; Ali, Waqar; Afzal, Bilal; Qazi, Nadia; Askar, Ghazan (Journal of Postgraduate Medical Institute, 2022)
Objective: To assess the availability of illicit tobacco products in online and local market in Pakistan. Methodology: We conducted a cross sectional study involving Pakistani online retailers. We used the “Google Search” function to identify the internet vendors, limiting the search to websites form Pakistan only. Out of a total of 100 websites, we selected 25 websites to place orders for tobacco products. These sites were selected on the basis of the volume of traffic to these sites. Out of the 25 selected websites only eight were functional at the time of data collection, so orders for the products were placed on these websites only. Additionally, some products were also procured from the local market in Peshawar for comparison with the products that were procured online. We analyzed each product using five-point criteria that has been used previously in the Pakistani context to assess illicit products and was developed in collaboration with the Tobacco Control Cell of Pakistan. SPSS Version 20 was used to analyze data in the form of frequencies and percentages. Results: Both Online and local products were found to be identical as per the 5 points of criteria with an almost equal percent of pictorial/text health warnings, under age warning, manufacturer’s name details and barcode/ retail price. Alarmingly just 31% and 33% of the products found online and locally respectively, had a pictorial health warning. 38% of the products procured online and 56% of the products sourced from the local market had warnings against under-age sale. Conclusion: A larger variety of tobacco products is available online as compared to the ones in local market, with a majority of the products being illicit.